Psychological Well-Being of Mental Health Nurses in the Time of Covid 19: Systematic Literature Review - Aswin Hardi; Mustikasari Mustikasari; Ria Utami Panjaitan; Herni Susanti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
During the COVID-19 pandemic, the psychological well-being of nurses is at stake. As nurses, especially mental health nurses, the stressful environment around day-to-day care and additional work in addition to nursing care and inaccuracies in how to cope with problems that arose during the pandemic, left mental health nurses psychologically burdened. The research method used in this study is a systematic approach adopted for the literature review. Databases searched include SCIENCE DIRECT, SCOPUS, SPINGERLINK, TAYLOR & FRANCIS, and WILEY. The search was conducted from September 2022 to December 2022. Strict criteria were given that the study must examine the psychological well-being status of mental health nurses during COVID-19; It must be stated that the mental health nurse in question is a nurse who works in mental health services, including in hospitals and communities; using quantitative and qualitative methods as well as mix methods must be published in English: and the required studies were published in March 2020 to 2022. All 10 articles were included in the review to be assessed for quality. For data analysis, a deductive approach is carried out according to the theory of psychological well-being, and content analysis is carried out, namely grouping categories after the integration of quantitative evidence, qualitative, mixed methods, and then categorial synthesis is carried out. The results of this study stated that the initial search resulted in a total of 7,752 publications, ultimately resulting in 10 studies reviewed, in the form of 6 quantitative studies, 3 mixed methods studies, and 1 qualitative study. Six (6) categories are arranged according to Ryff's theory of psychological well-being: autonomy, environmental mastery, self-development, positive relationships with others, purpose in life, and self-acceptance. The studies reviewed show that the efforts made by mental health nurses in providing nursing care in accordance with COVID-19 prevention and control programs have shown success in maintaining the psychological well-being status of mental nurses Keyword: COVID-19, Nurse Mental Health, Psychological well-being